Trend of Increasing Prevalence of Obesity in Women of Reproductive Age in Indonesia: Analysis of IFLS Survey Data (1993-2014) by Age Group - Dungga, Elvie Febriani; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
The escalating prevalence of overweight among women of reproductive age in Indonesia has emerged as a critical public health challenge. This study aims to analyze temporal trends in overweight prevalence among Indonesian women aged 15–49 years and investigate age-specific risk patterns using nationally representative longitudinal data. Utilizing the Indonesia Family Life Survey (IFLS) across all five waves (1993–2014), we extracted anthropometric, demographic, and socioeconomic data from the USbook health examination module. A total of 53,348 observations were analyzed after excluding outliers, with overweight defined as BMI ≥25 kg/m². Univariable logistic regression was employed to finding. The result demonstrated a marked increase in overweight prevalence from 18.8% (947/5,038) in 1993 to 38.3% (5,094/13,290) in 2014. While the highest prevalence initially clustered in women aged 35–39 years (1993–2007), a notable shift occurred in 2014, with the 30–34-year cohort surpassing other groups. Regression analysis revealed a significant age-gradient association, peaking at ages 40–44 (OR: 2.14, 95% CI: 1.89–2.43, p<0.001), suggesting heightened vulnerability in this demographic despite younger cohorts exhibiting faster prevalence growth. These findings underscore the dual burden of overweight among Indonesian women: an expanding younger population with rising incidence and persistently elevated risk in perimenopausal groups. The study advocates for life-course-targeted interventions prioritizing women aged 40–44 while addressing upstream determinants across reproductive-age populations. This longitudinal evidence provides critical insights for policymakers to design age-stratified strategies combating Indonesia’s overweight epidemic.